2013
DOI: 10.1002/pssa.201330233
|View full text |Cite
|
Sign up to set email alerts
|

Role of metal/silicon semiconductor contact engineering for enhanced output current in micro‐sized microbial fuel cells

Abstract: We show that contact engineering plays an important role to extract the maximum performance from energy harvesters like microbial fuel cells (MFCs). We experimented with Schottky and Ohmic methods of fabricating contact areas on silicon in an MFC contact material study. We utilized the industry standard contact material, aluminum, as well as a metal, whose silicide has recently been recognized for its improved performance in smallest scale integration requirements, cobalt. Our study shows that improvements in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…As expected, ohmic contact materials outperformed their Schottky counterparts in current production and in some instances in power as well. In particular, ohmic Al contacts produced the highest current whereas ohmic Co contacts are considered preferable for compatibility with integrated circuits for the smallest integration requirements 36. The study showed that improvements in contact engineering are important for device engineering and for microsystems.…”
Section: Microfabricated Mfcsmentioning
confidence: 95%
See 1 more Smart Citation
“…As expected, ohmic contact materials outperformed their Schottky counterparts in current production and in some instances in power as well. In particular, ohmic Al contacts produced the highest current whereas ohmic Co contacts are considered preferable for compatibility with integrated circuits for the smallest integration requirements 36. The study showed that improvements in contact engineering are important for device engineering and for microsystems.…”
Section: Microfabricated Mfcsmentioning
confidence: 95%
“…35 With these concepts in mind, Mink et al. investigated the use of standard microfabrication techniques to reduce contact resistance 36. They used Al, another industry‐standard contact material, and Co, which can form a silicide with reduced resistance and improved contact performance.…”
Section: Microfabricated Mfcsmentioning
confidence: 99%